2016
DOI: 10.1021/acs.energyfuels.5b02130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen Availability on off-Gassing Rates of Emissions from Stored Wood Pellets

Abstract: The phenomenon of off-gassing from wood pellets during storage has been the cause of several, in some cases fatal, accidents due to toxic atmospheres in storages. To optimize safety measures the nature of the responsible processes needs to be clarified. In this study the impact of O 2 availability, which is a decisive factor for the presumed oxidation of fatty acids, is pointed out. Off-gassing rates of CO, CO 2 , VOC, and CH 4 of pellets at relatively constant O 2 levels of approximately 35%, 20%, and <1% ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…This was possibly due to condensation onto the solid product because no increase with time was found for either new or already existing possible secondary reaction products. Also, Meier et al found a reducing trend in total VOCs in wood pellets during low-ventilation storage, which is in accordance with the results presented here. The concentrations of lower weight compounds were more stable over time, and off-gassing from pre-press samples changed less with storage time compared to direct and pellet samples.…”
Section: Resultssupporting
confidence: 92%
“…This was possibly due to condensation onto the solid product because no increase with time was found for either new or already existing possible secondary reaction products. Also, Meier et al found a reducing trend in total VOCs in wood pellets during low-ventilation storage, which is in accordance with the results presented here. The concentrations of lower weight compounds were more stable over time, and off-gassing from pre-press samples changed less with storage time compared to direct and pellet samples.…”
Section: Resultssupporting
confidence: 92%
“…Wallace et al found that for most homes air change rates, assuming windows closed, ranged from 0.30 to 1.9 (Wallace et al, 2002;Howard-Reed et al, 2002) per hour. Given the published offgassing rates of CO from pellets in the range of 10 −5 mg CO/kg pellets/min, a relatively small amount of ventilation can provide protective measures (Meier et al, 2016;Soto-Garcia et al, 2015b;Fan and Bi, 2013;Kuang et al, 2009). Hence, from these data, it appears that most homes had infiltration rates that may have helped maintain the low CO concentrations.…”
Section: Indoor Pellet Storagementioning
confidence: 99%
“…The topic has been investigated in several recent publications, e.g. [6,7] but the exact nature of the chemical processes at play do still not appear to be well-understood.…”
Section: Wood Pellet Chemical Off-gassing Risksmentioning
confidence: 99%